Depression - Spilsbury, Richard, 1963- (Spilsbury, Richard, 1963- Genetic diseases and gene therapies., 2019)
Examines a variety of topics related to depression ranging from how the illness develops to possible treatments. Includes a glossary, resources for further information, and color photographs.